Adiksi Media Sosial Sebagai Penyebab Harga Diri Rendah Pada Usia Dewasa Muda - Arfianto, Muhammad Ari; Ibad, Muhammad Rosyidul; Widowati, Sri; Handayani, Ela (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
The use of social media has increased in the last few years. Social media has a negative impact on a person's self-esteem because they make social comparisons based on what they see on social media. This study aims to examine the relationship between the level of social media use and the level of self-esteem in young adults. The study used a cross-sectional approach, and the population in this study was college students (19-20 years old) in Malang, Indonesia. The sample consisted of 96 respondents, selected using purposive sampling. Respondents filled out the Bergen Social Media Addiction Scale (BSMAS) questionnaire and the Coopersmith Self-esteem Inventory (CSEI). Data were analyzed using the Spearman Rank correlation test in SPSS. The results showed that 57.3% of respondents were at the alert category level of social media use, and 63.5% of respondents had very low self-esteem. The correlation test showed a negative relationship between social media use and self-esteem (p-value = 0.044; r = -0.206). The strength of the relationship is weak and has a negative direction, meaning that the higher the level of social media use, the lower the self-esteem level will be. Alert-level social media use among young adults has an effect on low levels of self-esteem.